1999
DOI: 10.1902/jop.1999.70.11.1355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Periodontitis and Smoking on Blood Leukocytes and Acute‐Phase Proteins

Abstract: In general, the combination of periodontitis and cigarette smoking alters the parameters studied. The effects of periodontitis on CRP and IgG2 means that periodontal lesions may also leak agents, priming the peripheral neutrophils to increased CL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
123
3
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 18 publications
14
123
3
5
Order By: Relevance
“…So it is plausible that CAL is not a suitable variable to investigate the association with periodontal disease and CRP levels. On the other hand, there are two studies that diagnosed periodontal disease with clinical attachment loss [13,28]. These studies reported a positive relation with CAL and CRP levels unlike the result of the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…So it is plausible that CAL is not a suitable variable to investigate the association with periodontal disease and CRP levels. On the other hand, there are two studies that diagnosed periodontal disease with clinical attachment loss [13,28]. These studies reported a positive relation with CAL and CRP levels unlike the result of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Elevated WBC in patients with periodontitis have been reported in some studies [19,27,28]. Kweider et al [19] were the first to report higher numbers of WBC in periodontitis (8.7 × 10 3 cells/μL in patients in comparison to 6.0 × 10 3 cell/μL in controls).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several mechanisms may explain the significant relationship between cigarette smoking and CRP concentrations. Cigarette smoking promotes inflammation in the oral cavity and airway tract, leading to periodontitis and chronic bronchitis (26,27). Also, free radicals generated by cigarette smoking can induce the production of inflammatory cytokines and consequently elevate CRP concentrations, as mentioned earlier (28).…”
Section: Discussionmentioning
confidence: 99%
“…Estos bajos niveles de bacteriemia pueden contribuir al incremento sistémico de la respuesta inmune e inflamatoria (40,41). La proximidad de dichos patóge-nos con el endotelio vascular, permite que tanto bacterias como moléculas proinflamatorias accedan a la circulación a través de las capas epiteliales quienes pueden haber perdido parte de su integridad por los procesos inflamatorios e infecciosos característicos de esta entidad (42).…”
Section: El Amiloide a Sérico Y Su Relación Con Enfermedad Periodontalunclassified